The Isolation and Identification of Pseudoalteromonas sp. H27, a Bacterial Strain Pathogenic to Crassostrea gigas - Heyang Qin; Junyi Jiang; Zhikai Jing; Jiayu Wang; Shuang Xu; Rongwei Chen; Bo Wang; Zhongming Huo; Lei Fang (Microorganisms, 2025)
Bacterial infection is frequently observed in disease outbreaks of aquatic animals, making it of significance to isolate and identify the bacterial pathogens. In this study, diseased individuals of Crassostrea gigas were sampled from the nearshore area in Zhanjiang, Guangdong in May 2023. Culturable bacteria were isolated from the diseased tissue and a pathogenic strain labeled as H27 was screened through a hemolysis test and bacterial challenge experiments. Morphological characterization, 16S rRNA gene sequence-based molecular identification and biochemical tests showed that strain H27 belonged to the genus of Pseudoalteromonas, a dominant genus in the diseased tissue of C. gigas revealed by bacterial community structure analysis. The clinical signs originally observed in naturally diseased C. gigas were reproduced in strain H27-challenged adults, both with the red mantle and adductor. Histopathological analysis was further performed on the diseased tissues of the latter, which showed a significantly increased accumulation of pigment granules in the cytoplasm of the diseased mantle as well as enlarged muscle fiber distances in the diseased adductor. In addition, strain H27 was re-isolated from tissues of the moribund C. gigas after bacterial challenge, indicating the fulfillment of Koch’s postulate. Our results help to enrich the knowledge of C. gigas diseases, possibly contributing to disease prevention and control.